Penal Realm in disciplinary proceedings of Police Organization - ali afrasiabi; adel sarikhani (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2015)
According European Court of Human rights interpretation on section 6 of European convention of fundamental rights, “penal realm” interred legal texts. In light of this legal institution, hearing process of offences naturally have penal sanctions must be done in observance of fair trial requirements. This paper attempt to answer two questions: which Police disciplinary offenses can inter penal realm? Is process of hearings in semi judicial commissions in police Organization accord whit fair trial requirements? This Research firstly considers penal realm criteria and kinds of disciplinary sanctions in Police organization to identify which sanctions included in penal realm. After identifying offenses included in penal realm, the Paper considers hearing process of Police disciplinary commissions to answer second question and identify defects current in provisions and practices. In next game through identifying conditions of current situation, the Paper gives resolution to achieve good situation. Paper findings identify 10 disciplinary offences can be categorized in penal realm and hearing process of these offences must be done with consideration of fair trial requirements. In current provisions and practices, impartiality of hearing entity and defensive right of suspect extremely violated. In order to achieve good model, that is necessary amendment of provisions and executive practices to enhance defensive rights and create impartial hearing entity for proceeding offenses that police staffs suspect commit them.